Sosialisasi Pemanfaatan Canva dan Quizziz dalam Pembelajaran - Ni Luh Gede Meilantari; I Wayan Wahyu Cipta Widiastika; I Gede Arya Weda; Khazya Nanda Suryo Atmojo; I Ketut Adi Putra Bonitu (Jurnal Pengabdian Kepada Masyarakat, 2024)
Quality basic education is inextricably linked to teacher competence. Competence is a person's ability or capability to perform a task based on his abilities. However, following the Covid-19 pandemic, many schools, including instructors, are struggling to adapt to the New Normal Era. One of these is elementary School No. 11 Dauh Puri, one of Denpasar's public elementary schools. Most teachers are elderly, and professional skill is required to design instructional media in a creative manner. One of the issues of Elementary School 11 Dauh Puri is teacher competence. Teachers lack the necessary expertise in science and technology to create engaging learning materials, particularly for foreign languages, that spark student interest. One of the methods proposed for improving teacher abilities is to provide training in the use of Canva as learning materials as well as the usage of Quizziz for assessment or evaluation of student learning. Teachers appreciate community service, which includes the use of Canva and Quizziz to create teaching materials. Despite the fact that she had official training, the teacher feels helped.